Real-Time Shear Wave Elastography for Determining the Ideal Site of Liver Biopsy in Diffuse Liver Disease - Yashwant Patidar; Jitender Singh; Navojit Chatterjee; Amar Mukund; Archana Rastogi; Guresh Kumar; Manoj Kumar Sharma (Indian Journal of Radiology and Imaging, 2024)
Objectives The objective of the study was to identify accurate site of liver biopsy under ultrasound and elastography guidance and compare the shear wave elastography (SWE) and transient elastography (TE) diagnostic accuracy with histopathological correlation.